2022
DOI: 10.1101/2022.07.20.500773
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pore-forming protein βγ-CAT drives extracellular nutrient scavenging under cell starvation

Abstract: Nutrient acquisition is essential for cells. βγ-CAT is a pore-forming protein (PFP) and trefoil factor complex assembled under tight regulation identified in toad Bombina maxima. Here, we reported that B. maxima cells secreted βγ-CAT under glucose and glutamine deficiency to scavenge extracellular proteins for their nutrient supply and survival. AMP-activated kinase signaling positively regulated the expression and secretion of βγ-CAT. The PFP complex promoted albumin and ovalbumin uptake through endolysosomal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…In addition to playing an important anti-microbial role, our recent studies also showed that the B. maxima af-PFP complex βγ-CAT can promote tissue repair, 44 help toads maintain water balance under osmotic stress, 45 and acquire or deliver nutrients under starvation conditions. 14,15 These findings suggested that af-PFPs may play multiple roles in toads depending on environmental conditions. Similarly, transcriptomic analysis of LIN-24 RNAi and LIN-24-OE worms showed that LIN-24 is involved in pathways other than those associated with the immune response, such as longevity regulation, fatty acid degradation, membrane transport, oxidoreductase regulation, and metabolism (Figures 2 and 6).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In addition to playing an important anti-microbial role, our recent studies also showed that the B. maxima af-PFP complex βγ-CAT can promote tissue repair, 44 help toads maintain water balance under osmotic stress, 45 and acquire or deliver nutrients under starvation conditions. 14,15 These findings suggested that af-PFPs may play multiple roles in toads depending on environmental conditions. Similarly, transcriptomic analysis of LIN-24 RNAi and LIN-24-OE worms showed that LIN-24 is involved in pathways other than those associated with the immune response, such as longevity regulation, fatty acid degradation, membrane transport, oxidoreductase regulation, and metabolism (Figures 2 and 6).…”
Section: Discussionmentioning
confidence: 92%
“…Ep37 has been suggested to be related to newt development, 4 and we recently found that βγ-CAT helps protect animals and cells against metabolic stresses such as starvation. 14,15 Overexpression of a flower-specific af-PFP from the dioecious plant Rumex acetosa alters flower development and induces male sterility in transgenic tobacco. 16 However, due to the existence of numerous isoforms within the same species and lack of specific tools such as antibodies or probes, 11 the physiological roles of af-PFPs are difficult to systematically investigate in these species.…”
Section: Introductionmentioning
confidence: 99%
“…Cell membranes with their selective permeability form barriers for molecule exchange between the cytosol and the extracellular environment ( 37 , 38 ). Toad B. maxima PFP complex βγ-CAT is a secretory endolysosome channel protein that has evolved to facilitate cell nutrient and water acquisition and transcellular transport while fulfilling immune defense (( 24 , 25 , 26 , 27 , 31 )). Considering the primary functions of βγ-CAT in B. maxima , there must be endogenous elements in the toad to regulate assembly and dissociation of this PFP complex, which guarantee its specific and controllable biological actions.…”
Section: Discussionmentioning
confidence: 99%
“…BmTFF3 functions in this PFP complex by acting as a chaperon that stabilizes the BmALP1 monomer and delivers BmALP1 to proper membrane targets via a double-receptor binding model ( 23 , 32 ). Toad B. maxima βγ-CAT is natural example that a TFF can form a PFP complex machine working in extracellular molecule uptake and transport between a cell and the extracellular environment (( 14 , 24 , 25 , 26 , 27 , 31 )). Considering the high conservation and functions of TFFs in vertebrates ( 46 , 48 , 50 , 61 , 62 , 63 , 64 ), our results provide new information on their first-hand actions and mechanisms involved in participating in novel PFP functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation